SARS-COV-2 manifestations among Madinah district patients, Basrah, IRAQ - Haider Kadhem Saeed; Ziyad Tariq Malghooth; Rafad Abdulazeez Abduljaleel (Zien Journals, 2023)
To evaluate the demographic manifestation of COVID-19 infections in Madinah district, Basrah province, Iraq in regards of age, gender, occupation, place of residence, travel history, contact with COVID19 patients, presence of chronic illness especially cardiovascular disease, hypertension, Diabetes Mellitus
Keywords: COVID-19; common; patients